2021
DOI: 10.1371/journal.ppat.1009774
|View full text |Cite
|
Sign up to set email alerts
|

Aryl hydrocarbon receptor activation by Lactobacillus reuteri tryptophan metabolism alleviates Escherichia coli-induced mastitis in mice

Abstract: The intestinal microbiota has been associated with the occurrence and development of mastitis, which is one of the most serious diseases of lactating women and female animals, but the underlying mechanism has not yet been elucidated. Aryl hydrocarbon receptor (AhR) activation by microbiota tryptophan metabolism-derived ligands is involved in maintaining host homeostasis and resisting diseases. We investigated whether AhR activation by microbiota-metabolic ligands could influence mastitis development in mice. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
102
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 78 publications
(115 citation statements)
references
References 49 publications
3
102
0
Order By: Relevance
“…Recent studies have shown that the occurrence of mastitis is accompanied by changes in gut microbiota in dairy cows ( 11 ). Our previous studies also indicated that gut microbiota disturbance contributes to the development of mastitis induced by S. aureus or E. coli in mice ( 12 , 13 ). Ma et al ( 14 ) showed that fecal microbiota transplantation from cows with mastitis to germfree mice results in mastitis.…”
Section: Introductionmentioning
confidence: 83%
“…Recent studies have shown that the occurrence of mastitis is accompanied by changes in gut microbiota in dairy cows ( 11 ). Our previous studies also indicated that gut microbiota disturbance contributes to the development of mastitis induced by S. aureus or E. coli in mice ( 12 , 13 ). Ma et al ( 14 ) showed that fecal microbiota transplantation from cows with mastitis to germfree mice results in mastitis.…”
Section: Introductionmentioning
confidence: 83%
“…Inflammation was involved in the development of mastitis (17). The invading bacteria could activate the innate immune system and lead to the production of inflammatory and oxidative mediators (18).…”
Section: Discussionmentioning
confidence: 99%
“…Mammary disease is a disease with a serious pathological process and complicated influencing factors [ 22 , 23 ]. Finding ways in which to prevent mammary disease and protect mammary health is a problem to be solved.…”
Section: Discussionmentioning
confidence: 99%